Metabolic aspects of phenolic compounds from Triplaris gardneriana seeds in the management of oxidative stress. (2nd June 2020) - Lopes Neto, José Joaquim; de Almeida, Thiago Silva; Gonçalves de Lima, Rita de Cássia; dos Santos Nunes, Ricardo Gomes; de Lima Silva, Jailson Renato; de Almeida, Lécio Leone; Kamdem, Jean Paul; Carvalho, Ana Fontenele Urano
Abstract: Objective: Considering the limited number of studies that analyze the behavior of plant preparations in human body, this study aimed to characterize the phenolic compounds from Triplaris gardneriana extract (EETg) in terms of antioxidant and metabolic aspects, integrating in vitro, in silico and in vivo strategies. Methods: EETg was analyzed in relation to polyphenols release from the plant matrix under in vitro digestion, as well as the pharmacokinetic prediction of their major compounds by in silico simulation and understanding of its in vivo antioxidant effect in an alternative animal model. Results: About 35.22% of polyphenols from EETg proved to be accessible after enzymatic hydrolysis. A kinetics study showed that 40% of the total content of these phytochemicals was released from the extract accompanied by increased antioxidant capacity after 180 min of gastrointestinal simulation. A computational approach revealed that 7 out of 9 major phenolic compounds of EETg showed good pharmacokinetic parameters such as intestinal absorption and bioavailability score. In addition, the extract showed a protective effect on copper-induced oxidative stress in Drosophila melanogaster, evidenced by the restoration of basal levels of thiol and malondialdehyde contents. These biochemical observations were supported by the examination of histological features of D . melanogaster brain. Conclusion: It was demonstrated that the oral administration of EETg would provide phenolic compounds partially absorbable by the human gut and capable of providing health benefits associated with the inhibition of oxidative stress. Additionally, the results highlight the need to implement new approaches for the rational development of plant-based medicines.